Characterization of Polylactic Acid/Chitosan/Cellulose Nanofibers for Wound Dressing Applications - Belinda Laulista; Desy Miftachul; Lilik Suprianti; Tri Widjaja; Aisyah Alifatul Zahidah Rohmah; Citra Yulia Sari (Eksergi, 2026)
Effective wound care requires dressing materials that provide physical protection while actively encouraging tissue regeneration. This research investigates the development and characterization of biocomposite nanofiber membranes composed of polylactic acid (PLA), chitosan, and cellulose, synthesized via the electrospinning method at an optimized operating voltage of 20 kV. The study aimed to identify the optimal material ratio that balances mechanical durability with surface wettability. Comprehensive evaluations included Scanning Electron Microscopy (SEM), Fourier Transform Infrared (FTIR), water contact angle (WCA) measurements, and mechanical testing. The results demonstrate that the integration of chitosan and cellulose significantly refined fiber morphology and wettability. The optimal variant with a composition of 90:5:5 wt.% (PLA:chitosan:cellulose) achieved a WCA of 98.64°, indicating that the hydrophobicity was maintained relative to pure PLA. M orphologically, the composite fibers were uniform and bead-less, with a mean diameter reduction of 36.2% (from 517.12 nm in pure PLA to 329.68 nm). FTIR spectra confirmed successful component incorporation through characteristic amide and hydroxyl bands. Mechanically, the composite membrane exhibited a superior synergy between strength and flexibility, achieving a yield strength of 0.06 MPa and a significant elongation at break of 80.36%. These findings suggest that the 90:5:5 formulation successfully bridges the gap between mechanical durability and the high surface area-to-volume ratio required for advanced, biodegradable wound care applications.